A core-shell type rare earth gradient doped positive electrode material and a preparation method and application thereof

CN121260764BActive Publication Date: 2026-10-16GEM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511376509.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-25
Publication Date
2026-10-16
Estimated Expiration
2045-09-25

AI Technical Summary

Technical Problem

高镍层状氧化物正极材料中镍含量超过80%,但镍含量超过80%时面临晶格氧释放导致热失控风险、阳离子混排阻碍锂离子扩散、以及H2-H3相变引发体积收缩造成循环微裂纹等固有缺陷

Benefits of technology

[0052] (1) Breakthrough in material performance: Synergistically achieve high specific capacity (significantly exceeding traditional processes) and ultra-long cycle life (cycle decay rate reduced by more than 50%), while simultaneously improving the thermal safety threshold (thermal runaway initiation temperature increased by more than 20%).

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005612945000000131
    Figure BDA0005612945000000131
  • Figure BDA0005612945000000141
    Figure BDA0005612945000000141
Patent Text Reader

Abstract

The application provides a core-shell rare earth gradient doped positive electrode material and a preparation method and application thereof, and the preparation method comprises the following steps: introducing a mixed metal source solution and a first complexing agent into a mixed solvent, performing a solvothermal reaction to obtain a core precursor, then continuing to heat to a first temperature, introducing a rare earth doping source solution, continuing to heat to a second temperature for heat preservation, and finally performing rapid cooling to obtain a precursor material; mixing and sintering a lithium source and the precursor material to obtain the core-shell rare earth gradient doped positive electrode material. The preparation method synchronously controls the coprecipitation reaction kinetics and the gradient locking process through a mixed solvent system, avoids composition segregation, triggers lattice distortion through a solvothermal system, induces rare earth element gradient doping, breaks through the interface mutation defects of the traditional core-shell structure, and synchronously realizes the synchronous improvement of high specific capacity and super-long cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery technology and relates to a core-shell rare earth gradient doped cathode material, its preparation method and application. Background Technology

[0002] High-nickel layered oxide cathode materials have become core materials for improving the energy density of lithium-ion batteries due to their high specific capacity and high operating voltage. High-nickel layered oxide cathode materials contain more than 80% nickel, but when the nickel content exceeds 80%, they face inherent defects such as the risk of thermal runaway caused by lattice oxygen release, cation mixing hindering lithium-ion diffusion, and volume shrinkage caused by H2-H3 phase transition resulting in cycling microcracks.

[0003] Existing modification technologies mainly employ two approaches: gradient structure design and element doping. Gradient design improves stability by adjusting the concentration distribution of transition metals, but the core-shell structure synthesized by traditional co-precipitation methods exhibits abrupt compositional changes at the interface. During cycling, stress concentration leads to particle breakage, and a single solvent system cannot balance the metal precipitation kinetics, resulting in excessively high manganese dissolution rates. Element doping (such as Mg / Al) can suppress cation mixing, but solid-phase doping easily leads to localized element enrichment, and high-temperature sintering causes manganese dissolution, thereby triggering Mn dissolution. 3+ The disproportionation reaction exacerbates phase transformation degradation, and the forced sacrifice of effective nickel content to maintain structural stability leads to a decrease in specific capacity. In addition, existing processes cannot achieve submicron-level continuous concentration gradients, requiring high precision in multi-step control, with solvent utilization rates of less than 60% per pass, significantly increasing costs. Furthermore, high-temperature, long-duration sintering causes abnormal grain growth and lithium volatilization, ultimately making it difficult to maintain the integrity of the bulk structure and the stability of the surface and interface of the material.

[0004] Therefore, none of the above methods have resolved the contradiction between gradient continuity and process controllability. That is, existing technologies cannot achieve submicron level continuous concentration gradients, and there is also the contradiction between high nickel activity and structural stability. In other words, doping or coating in existing technologies will sacrifice effective nickel content and reduce specific capacity.

[0005] Based on the above research, there is a need to provide a method for preparing cathode materials. This method can overcome the interface abrupt defects of traditional core-shell structures, achieve elemental gradient doping, and avoid elemental segregation. Summary of the Invention

[0006] The purpose of this invention is to provide a core-shell rare earth gradient-doped cathode material, its preparation method, and its application. The preparation method uses a mixed solvent system to simultaneously control the co-precipitation reaction kinetics and gradient locking process, avoiding the component segregation caused by traditional multi-solvent switching. It uses a solvothermal system to trigger lattice distortion and induce rare earth element gradient doping, overcoming the interface abrupt defects of traditional core-shell structures, and synergistically achieving a simultaneous improvement in high specific capacity and ultra-long cycle life.

[0007] To achieve this objective, the present invention adopts the following technical solution:

[0008] In a first aspect, the present invention provides a method for preparing a core-shell rare-earth gradient-doped cathode material, the method comprising the following steps:

[0009] (1) The mixed metal source solution and the first complexing agent are introduced into the mixed solvent to carry out a solvothermal reaction to obtain the core precursor. Then, when the temperature is raised to the first temperature, the rare earth doped source solution is introduced. The temperature is then raised to the second temperature and held. Finally, the temperature is rapidly cooled to obtain the precursor material.

[0010] The mixed solvent includes a second complexing agent, an alkanolamine solvent, and a diol solvent; the first temperature is above 150°C, and the second temperature is above 180°C;

[0011] (2) Mix and sinter the lithium source and the precursor material described in step (1) to obtain the core-shell rare earth gradient doped cathode material.

[0012] This invention employs a solvothermal method to prepare precursor materials. The preparation utilizes a ternary solvent system comprising a second complexing agent, an alkanolamine solvent, and a diol solvent. This integrates precursor synthesis, gradient doping, and structure locking within the same solvothermal system. The ternary solvent system simultaneously regulates the coprecipitation reaction kinetics and the gradient locking process, avoiding component segregation caused by switching between multiple solvents. When the temperature reaches the first temperature, a rare-earth doping source solution is introduced to achieve doping. The temperature is then raised to a second temperature and held to trigger lattice distortion (in-situ XRD monitoring shows c-axis shrinkage). This invention induces a continuous concentration gradient distribution of rare earth elements along the particle diameter, overcoming the interface abrupt defects of traditional core-shell structures. Finally, rapid cooling solidifies the metastable structure of lattice distortion, achieving atomic-level gradient distribution fixation and thus locking the structure. Therefore, this invention successfully constructs a submicron-level continuous concentration gradient, effectively suppressing the initiation of cyclic cracks. The integrated solvothermal process shortens the production cycle by more than 40%, reduces energy consumption, improves raw material utilization, and synergistically achieves high specific capacity and ultra-long cycle life, while simultaneously improving the thermal safety threshold.

[0013] The first temperature is above 150°C, for example, it can be 150°C, 160°C, 170°C, 180°C, 190°C or 200°C, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable. Preferably, it is 150-170°C, and more preferably, it is 158-162°C.

[0014] The second temperature is above 180°C, for example, it can be 180°C, 185°C, 190°C, 195°C or 200°C, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable. Preferably, it is 180-200°C, and more preferably, it is 188-192°C.

[0015] This invention achieves elemental gradient doping through staged heating. In the first stage, a rare earth doping source solution is introduced at a specific temperature. If the temperature is too low, the activation energy for ion migration is insufficient, the rare earth diffusion barrier is not broken, and insufficient rare earth ion diffusion leads to a discontinuous gradient distribution. If the temperature is too high, the channels close, the BET decreases, and the doping effect is affected. In the second stage, after introducing the rare earth doping source solution, the temperature is further increased to trigger the lattice distortion effect. If the holding temperature in the second stage is too low, the lattice distortion energy is insufficient, and gradient locking fails. If the holding temperature in the second stage is too high, the grains coarsen, which will destroy the integrity of the structure.

[0016] Preferably, the time for heating to the second temperature and holding it in step (1) is 230-250 min, for example, it can be 230 min, 235 min, 240 min, 245 min or 250 min, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0017] Preferably, the cooling rate of the rapid cooling in step (1) is ≥8℃ / s, for example, it can be 8℃ / s, 8.5℃ / s, 9℃ / s, 9.5℃ / s, 10℃ / s, 10.5℃ / s or 11℃ / s, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0018] Preferably, the heating rate in step (1) to continue heating to the first temperature is 2-4℃ / min, for example, it can be 2℃ / min, 2.5℃ / min, 3℃ / min, 3.5℃ / min or 4℃ / min, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0019] Preferably, the flow rate of the rare earth doped source solution in step (1) is 0.9-1.1 mL / min, for example, it can be 0.9 mL / min, 0.95 mL / min, 1.0 mL / min, 1.05 mL / min or 1.1 mL / min, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0020] Preferably, the rare earth doped source solution in step (1) includes La ions and Yb ions.

[0021] Preferably, in the rare earth doped source solution in step (1), the molar ratio of La ions to Yb ions is (1.8-2.2):1, for example, it can be 1.8:1, 1.9:1, 2.0:1, 2.1:1 or 2.2:1, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0022] Preferably, the total metal ion concentration of the rare earth doped source solution in step (1) is 0.75-0.85 mol / L, for example, it can be 0.75 mol / L, 0.77 mol / L, 0.79 mol / L, 0.81 mol / L, 0.83 mol / L or 0.85 mol / L, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0023] Preferably, in step (1), the second complexing agent comprises ammonia.

[0024] Preferably, the amine solvent in step (1) includes any one or a combination of at least two of ethanolamine, diethanolamine or triethanolamine.

[0025] Preferably, the diol solvent in step (1) includes any one or a combination of at least two of ethylene glycol, propylene glycol, or butanediol.

[0026] Preferably, the mixed solvent in step (1) includes a second complexing agent, an alkanolamine solvent, and a diol solvent in a volume ratio of (2.5-3.5):(0.7-1.5):(5.5-6.5), for example, 3:1.5:5.5, 2.5:1:6.5, or 3.5:0.7:5.8, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0027] Preferably, the pH of the mixed solvent in step (1) is 10.5-11.0, for example, it can be 10.5, 10.6, 10.7, 10.8, 10.9 or 11, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0028] The present invention involves preparing a mixed solvent by combining a second complexing agent, an alkanolamine solvent, and a diol solvent, heating it to 78-82°C (e.g., 78°C, 79°C, 80°C, 81°C, or 82°C) and stirring it at 280-320 rpm (e.g., 280 rpm, 290 rpm, 300 rpm, 310 rpm, or 320 rpm), and automatically titrating ammonia water to adjust the pH to 10.5-11.0 (e.g., 10.5, 10.6, 10.7, 10.8, 10.9, or 11).

[0029] Preferably, the mixed metal source solution in step (1) includes a nickel-cobalt-manganese co-extraction solution obtained from the recycling of waste batteries.

[0030] The mixed metal source solution described in this invention is a nickel-cobalt-manganese co-extraction solution obtained by extracting waste battery recycled materials (after membrane filtration to remove impurities and supplementing with elemental salt solution). Therefore, this invention uses a three-step fine-tuning technology of solvent extraction co-extraction solution followed by membrane filtration, concentration calibration, and elemental salt supplementation to accurately match the proportion of recovered metal ions and maximize the value of recovered metals.

[0031] Preferably, in the mixed metal source solution described in step (1), the molar ratio of nickel ions, cobalt ions, and manganese ions is (7.95-8.05):(0.95-1.05):(0.95-1.05), for example, it can be 8:1:1, 7.95:1.05:1, or 8.05:1:0.95, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0032] Preferably, the flow rate of the mixed metal source solution in step (1) is 1.8-2.2 mL / min, for example, it can be 1.8 mL / min, 1.9 mL / min, 2.0 mL / min, 2.1 mL / min or 2.2 mL / min, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0033] Preferably, the concentration of the first complexing agent in step (1) is 0.4-0.6 mol / L, for example, it can be 0.4 mol / L, 0.45 mol / L, 0.5 mol / L, 0.55 mol / L or 0.6 mol / L, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0034] Preferably, in step (1), the first complexing agent comprises a citric acid solution and / or a tartaric acid solution.

[0035] Preferably, the temperature of the solvothermal reaction in step (1) is 78-82°C, for example, 78°C, 79°C, 80°C, 81°C or 82°C, and the time is 170-190 min, for example, 170 min, 175 min, 180 min, 185 min or 190 min, but not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0036] Preferably, the pH of the solvothermal reaction system in step (1) is 10.8-11.2, for example, it can be 10.8, 10.8, 10.9, 11.0, 11.1 or 11.2, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0037] Preferably, the particle size D50 of the core precursor in step (1) is 3.2-4.0 μm, for example, it can be 3.2 μm, 3.4 μm, 3.6 μm, 3.8 μm or 4.0 μm, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0038] Preferably, after the rapid cooling in step (1), centrifugal washing and vacuum drying are also performed.

[0039] Preferably, the centrifugal washing speed is 7500-8500 rpm, for example, it can be 7500 rpm, 7700 rpm, 7900 rpm, 8100 rpm, 8300 rpm or 8500 rpm, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0040] Preferably, the vacuum drying temperature is 75-85℃, for example, it can be 75℃, 77℃, 79℃, 81℃, 83℃ or 85℃, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0041] Preferably, the sintering in step (2) includes a first sintering in an air atmosphere, followed by switching to an oxygen atmosphere and continuing to heat up for a second sintering.

[0042] This invention first sintersects in air and then in oxygen. Specifically, the structure is first stabilized at low temperature in an oxygen-containing air atmosphere, and then crystallized at high temperature in an oxygen-rich environment to form the final product. This achieves synergistic control of bulk pre-oxidation and surface nickel-rich crystallization, resulting in a high-Ni surface. 3+ Proportion and low Li + Volatilization rate.

[0043] Preferably, the flow rate of the oxygen atmosphere is >4L / min, for example, it can be 4.5L / min, 5L / min, 5.5L / min, 6L / min, 6.5L / min or 7L / min, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0044] Preferably, the temperature of the first sintering is 380-420℃, for example, 380℃, 390℃, 400℃, 410℃ or 420℃, and the holding time is 3-5h, for example, 3h, 3.5h, 4h, 4.5h or 5h, but not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0045] Preferably, the temperature of the secondary sintering is 740-760℃, for example, 740℃, 745℃, 750℃, 755℃ or 760℃, and the holding time is 11-13h, for example, 11h, 12h or 13h, but not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0046] Preferably, the molar ratio of the lithium source in step (2) to the precursor material in step (1) is (1.03-1.08):1, for example, it can be 1.03:1, 1.04:1, 1.05:1, 1.06:1, 1.07:1 or 1.08:1, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0047] The preparation method of this invention first prepares a ternary mixed solvent system of ammonia-ethanolamine-ethylene glycol, mixes it in a specific ratio, heats it to a constant temperature range, maintains stirring, and adjusts the pH through automatic titration. Next, the nickel-cobalt-manganese co-extract extracted from the recovered material is precisely proportioned and a composite complexing agent is added simultaneously at a controlled flow rate to carry out a co-precipitation reaction, forming a nickel-cobalt-manganese core precursor with uniform particle size. Subsequently, the temperature is increased in stages, and a lanthanum-ytterbium rare earth solution is injected at a specified temperature point to achieve gradient doping. During the critical holding stage, a lattice distortion effect is triggered to promote the elemental gradient distribution, and the structure is locked by rapid cooling. The resulting precursor is centrifuged, washed, and vacuum dried, then mixed with a lithium source in a specific ratio and ball-milled. Finally, a two-stage gradient atmosphere sintering process is performed: first, the structure is stabilized at low temperature in an oxygen-containing atmosphere, and then the process is switched to a high-temperature crystallization environment in an oxygen-rich environment to form the final product.

[0048] In a second aspect, the present invention provides a core-shell rare earth gradient-doped cathode material, which is prepared by the preparation method described in the first aspect.

[0049] In the cathode material described in this invention, the concentration of rare earth doping elements gradually decreases from the surface of the material inwards.

[0050] Thirdly, the present invention provides a lithium-ion battery comprising a core-shell rare-earth gradient-doped cathode material as described in the second aspect.

[0051] Compared with the prior art, the present invention has the following beneficial effects:

[0052] (1) Breakthrough in material performance: Synergistically achieve high specific capacity (significantly exceeding traditional processes) and ultra-long cycle life (cycle decay rate reduced by more than 50%), while simultaneously improving the thermal safety threshold (thermal runaway initiation temperature increased by more than 20%).

[0053] (2) Structural innovation advantages: Successfully constructed a submicron level continuous concentration gradient (the thickness of the gradient transition layer is increased to twice that of the traditional core-shell structure), effectively suppressing the initiation of cyclic cracks (the density of microcracks is reduced by more than 80%).

[0054] (3) Process efficiency innovation: The integrated solvothermal process shortens the production cycle by more than 40%, reduces energy consumption, and improves utilization. Detailed Implementation

[0055] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0056] Example 1

[0057] This embodiment provides a method for preparing a core-shell rare-earth gradient-doped cathode material, the method comprising the following steps:

[0058] (1) Ammonia, ethanolamine and ethylene glycol were mixed in a volume ratio of 3:1:6 to form a mixed solvent. The mixture was heated to 80°C and stirred at 300 rpm. The pH was adjusted to 10.7 by automatic titration with ammonia. The nickel-cobalt-manganese co-extraction solution obtained by extraction of waste battery materials (after membrane filtration to remove impurities and replenishment with elemental salt solution, with a molar ratio of Ni ions, Co ions and Mn ions of 8:1:1) was simultaneously pumped into the mixed solvent at a flow rate of 2 mL / min along with a 0.5 mol / L citric acid-tartaric acid composite complexing agent (molar ratio of 1:1). The solvothermal reaction was carried out for 180 minutes to generate a core precursor with a D50 of 3.8 μm. The pH of the system during the reaction was in the range of 10.8-11.0.

[0059] (2) Then, the temperature was raised to 160℃ at a rate of 3℃ / min, and a La and Yb nitrate ethanol solution was injected at a flow rate of 1mL / min (the molar ratio of La ions to Yb ions was 2:1, and the total metal ion concentration was 0.8mol / L). The temperature was then raised to 190℃ and held for 240 minutes. Subsequently, the temperature was rapidly cooled at a rate of 9℃ / s to lock the gradient. The product was washed three times by centrifugation at 8000rpm and vacuum dried at 80℃ for 12 hours to obtain the precursor material.

[0060] (3) The precursor material and lithium hydroxide were ball-milled at a molar ratio of 1:1.05 (ball-to-material ratio 5:1, ball milling at 300 rpm for 2 hours), and then gradient sintering was performed: first, the temperature was raised to 400℃ at 2℃ / min and held for 4 hours in an air atmosphere, then the oxygen atmosphere was switched (flow rate of 5L / min) and the temperature was raised to 750℃ at 5℃ / min and held for 12 hours to obtain the core-shell rare earth gradient doped cathode material (La / Yb doped gradient material with nickel-rich active phase on the surface).

[0061] Example 2

[0062] This embodiment provides a method for preparing a core-shell rare-earth gradient-doped cathode material, the method comprising the following steps:

[0063] (1) Ammonia, ethanolamine and ethylene glycol were mixed in a volume ratio of 3.5:1:5.5 to prepare a mixed solvent. The mixture was heated to 78°C and stirred at 320 rpm. The pH was adjusted to 10.5 by automatic titration with ammonia. The nickel-cobalt-manganese co-extraction solution obtained by extraction of waste battery materials (after membrane filtration to remove impurities and replenishment with elemental salt solution, with a molar ratio of Ni ions, Co ions and Mn ions of 8.05:1:0.95) was simultaneously pumped into the mixed solvent at a flow rate of 1.8 mL / min along with a 0.6 mol / L citric acid-tartaric acid composite complexing agent (molar ratio of 1:1). The solvothermal reaction was carried out for 190 minutes to generate a core precursor with a D50 of 3.2 μm. The pH of the system during the reaction was in the range of 11.0-11.2.

[0064] (2) Then, the temperature was increased to 162℃ at a rate of 4℃ / min, and a La and Yb nitrate ethanol solution was injected at a flow rate of 0.9mL / min (the molar ratio of La ions to Yb ions was 1.8:1, and the total metal ion concentration was 0.85mol / L). The temperature was then increased to 188℃ and held for 250 minutes. Subsequently, the gradient was locked by rapid cooling at a rate of 8℃ / s. The product was washed three times by centrifugation at 7500rpm and vacuum dried at 85℃ for 12 hours to obtain the precursor material.

[0065] (3) The precursor material and lithium hydroxide were ball-milled at a molar ratio of 1:1.08 (ball-to-material ratio 5:1, ball milling at 300 rpm for 2 hours), and then gradient sintering was carried out: first, the temperature was raised to 420°C at 2°C / min and held for 3 hours in an air atmosphere, then the oxygen atmosphere was switched (flow rate of 4.5 L / min) and the temperature was raised to 760°C at 5°C / min and held for 11 hours to obtain the core-shell rare earth gradient doped cathode material (La / Yb doped gradient material with nickel-rich active phase on the surface).

[0066] Example 3

[0067] This embodiment provides a method for preparing a core-shell rare-earth gradient-doped cathode material, the method comprising the following steps:

[0068] (1) Ammonia, ethanolamine and ethylene glycol were mixed in a volume ratio of 2.5:1.5:6 to prepare a mixed solvent. The mixture was heated to 82°C and stirred at 280 rpm. The pH was adjusted to 11.0 by automatic titration with ammonia. The nickel-cobalt-manganese co-extraction solution obtained by extraction of waste battery materials (after membrane filtration to remove impurities and replenishment with elemental salt solution, with a molar ratio of Ni ions, Co ions and Mn ions of 8:0.95:1.05) was simultaneously pumped into the mixed solvent at a flow rate of 2.2 mL / min along with a 0.4 mol / L citric acid-tartaric acid composite complexing agent (molar ratio of 1:1). The solvothermal reaction was carried out for 170 minutes to generate a core precursor with a D50 of 4.0 μm. The pH of the system during the reaction was in the range of 10.8-11.0.

[0069] (2) Then, the temperature was increased to 158℃ at a rate of 2℃ / min, and a La and Yb nitrate ethanol solution was injected at a flow rate of 1.1mL / min (the molar ratio of La ions to Yb ions was 2.2:1, and the total metal ion concentration was 0.75mol / L). The temperature was then increased to 192℃ and held for 230 minutes. Subsequently, the gradient was locked by rapid cooling at a rate of 10℃ / s. The product was washed three times by centrifugation at 8500rpm and dried under vacuum at 75℃ for 12 hours to obtain the precursor material.

[0070] (3) The precursor material and lithium hydroxide were ball-milled at a molar ratio of 1:1.03 (ball-to-material ratio 5:1, ball milling at 300 rpm for 2 hours), and then gradient sintering was performed: first, the temperature was raised to 380℃ at 2℃ / min and held for 5 hours in an air atmosphere, then the oxygen atmosphere was switched (flow rate of 5L / min) and the temperature was raised to 740℃ at 5℃ / min and held for 13 hours to obtain the core-shell rare earth gradient doped cathode material (La / Yb doped gradient material with nickel-rich active phase on the surface).

[0071] Example 4

[0072] This embodiment provides a method for preparing a core-shell rare earth gradient doped cathode material. Except for step (2) where the temperature is raised to 150°C and a solution of La and Yb in nitrate ethanol is injected, the preparation method is the same as in Example 1.

[0073] Example 5

[0074] This embodiment provides a method for preparing a core-shell rare earth gradient doped cathode material. Except for step (2) where the temperature is raised to 170°C and a solution of La and Yb in nitrate ethanol is injected, the preparation method is the same as in Example 1.

[0075] Example 6

[0076] This embodiment provides a method for preparing a core-shell rare earth gradient doped cathode material. Except for step (2), which involves injecting a La and Yb nitrate ethanol solution and then heating the material to 180°C and holding it at that temperature for 240 minutes, the preparation method is the same as in Example 1.

[0077] Example 7

[0078] This embodiment provides a method for preparing a core-shell rare earth gradient doped cathode material. Except for step (2), which involves injecting a La and Yb nitrate ethanol solution and then heating the material to 200°C and holding it at that temperature for 240 minutes, the preparation method is the same as in Example 1.

[0079] Comparative Example 1

[0080] This comparative example provides a method for preparing a cathode material. Except for step (2), which involves heating the material to 140°C and then injecting a solution of La and Yb in nitrate ethanol, the preparation method is the same as in Example 1.

[0081] Comparative Example 2

[0082] This comparative example provides a method for preparing a cathode material. Except for step (2), after injecting the nitrate ethanol solution of La and Yb, the temperature is not raised and the material is kept at 160°C for 240 minutes. The rest of the preparation method is the same as in Example 1.

[0083] Comparative Example 3

[0084] This comparative example provides a method for preparing a cathode material. The preparation method is the same as that in Example 1, except that ethanolamine is not added to the mixed solvent in step (1).

[0085] Comparative Example 4

[0086] This comparative example provides a method for preparing a cathode material. The preparation method is the same as that in Example 1, except that ethylene glycol is not added to the mixed solvent in step (1).

[0087] The cathode materials obtained in the above embodiments and comparative examples were used to prepare cathode sheets, which were then assembled into batteries with lithium sheets, polypropylene separators, and lithium hexafluorophosphate electrolyte. The specific capacity, cycle performance, and thermal runaway initiation temperature of the batteries were tested under the following conditions:

[0088] (1) 1C First-Effect Capacity Test

[0089] Under constant temperature conditions, charge the battery at a constant current of 1C to the upper limit voltage, then switch to constant voltage charging until the current is ≤0.05C; after standing for 10 minutes, discharge it at a constant current of 1C to the cutoff voltage (e.g., 3.0V); perform three cycles to calculate the initial effective capacity.

[0090] (2) 500-week capacity retention test

[0091] In a constant temperature environment, the initial capacity of the battery was first measured, and then constant current charge-discharge cycles of 1C were performed for 500 cycles. The discharge capacity was measured after the 500th cycle.

[0092] (3) Thermal runaway initiation temperature test

[0093] Using an adiabatic calorimeter, the fully charged battery was programmed to heat up at a rate of 5°C / min, and the battery temperature was monitored in real time. The initiation temperature at which thermal runaway was triggered when the temperature rise rate at the monitoring point was ≥1°C / s and lasted for ≥3 seconds was the result.

[0094] The test results are shown in Table 1:

[0095] Table 1

[0096]

[0097]

[0098] As can be seen from Table 1:

[0099] As can be seen from Examples 1, 4-5, 6-7 and Comparative Example 1, the present invention achieves elemental gradient doping through staged heating. If the temperature in the first stage is too low or too high, or the temperature in the second stage is too low or too high, it will affect the gradient distribution of elements, thereby affecting the performance of the cathode material. As can be seen from Examples 1 and Comparative Example 2, the second stage of staged heating in the present invention triggers the lattice distortion effect, promoting rare earth element gradient doping. However, Comparative Example 2 did not further increase the temperature during gradient doping, which will affect the performance of the cathode material. As can be seen from Examples 1 and Comparative Examples 3-4, the mixed solvent of the present invention is a ternary solvent system. The integrated solvothermal process shortens the production cycle. The absence of any solvent will prevent the integrated solvothermal process from being achieved, which will affect the electrochemical performance of the cathode material.

[0100] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A method for preparing a core-shell rare-earth gradient-doped cathode material, characterized in that, The preparation method includes the following steps: (1) The mixed metal source solution and the first complexing agent are introduced into the mixed solvent to carry out a solvothermal reaction to obtain the core precursor. Then, when the temperature is raised to the first temperature, the rare earth doped source solution is introduced. The temperature is then raised to the second temperature and held. Finally, the temperature is rapidly cooled to obtain the precursor material. The mixed solvent includes a second complexing agent, an alkanolamine solvent, and a diol solvent; the first temperature is 150-170°C, and the second temperature is 180-200°C; Step (1) The first complexing agent comprises citric acid solution and / or tartaric acid solution; Step (1) The second complexing agent comprises ammonia water; The mixed metal source solution in step (1) includes nickel ions, cobalt ions and manganese ions, and the molar ratio of nickel ions, cobalt ions and manganese ions is (7.95-8.05):(0.95-1.05):(0.95-1.05); (2) Mix and sinter the lithium source and the precursor material described in step (1) to obtain the core-shell rare earth gradient doped cathode material.

2. The preparation method according to claim 1, characterized in that, Step (1) The first temperature is 158-162℃.

3. The preparation method according to claim 1, characterized in that, Step (1) The second temperature is 188-192℃.

4. The preparation method according to claim 1, characterized in that, The time for holding the temperature at the second temperature in step (1) is 230-250 minutes.

5. The preparation method according to claim 1, characterized in that, The cooling rate of the rapid cooling in step (1) is ≥8℃ / s.

6. The preparation method according to claim 1 or 2, characterized in that, The heating rate for continuing to heat to the first temperature in step (1) is 2-4℃ / min.

7. The preparation method according to claim 1, characterized in that, The flow rate of the rare earth doped source solution in step (1) is 0.9-1.1 mL / min.

8. The preparation method according to claim 1, characterized in that, The rare earth doped source solution in step (1) includes La ions and Yb ions.

9. The preparation method according to claim 8, characterized in that, In the rare earth doped source solution described in step (1), the molar ratio of La ions to Yb ions is (1.8-2.2):

1.

10. The preparation method according to claim 1, characterized in that, The total metal ion concentration of the rare earth doped source solution in step (1) is 0.75-0.85 mol / L.

11. The preparation method according to claim 1, characterized in that, The amine solvent in step (1) includes any one or a combination of at least two of ethanolamine, diethanolamine or triethanolamine.

12. The preparation method according to claim 1, characterized in that, The diol solvent in step (1) includes any one or a combination of at least two of ethylene glycol, propylene glycol, or butanediol.

13. The preparation method according to claim 1, characterized in that, The mixed solvent in step (1) includes a second complexing agent, an alkanolamine solvent, and a diol solvent in a volume ratio of (2.5-3.5):(0.7-1.5):(5.5-6.5).

14. The preparation method according to claim 1, characterized in that, The pH of the mixed solvent in step (1) is 10.5-11.

0.

15. The preparation method according to claim 1, characterized in that, The mixed metal source solution in step (1) includes a nickel-cobalt-manganese co-extraction solution obtained from the recycling of waste batteries.

16. The preparation method according to claim 1, characterized in that, The flow rate of the mixed metal source solution in step (1) is 1.8-2.2 mL / min.

17. The preparation method according to claim 1, characterized in that, Step (1) The concentration of the first complexing agent is 0.4-0.6 mol / L.

18. The preparation method according to claim 1, characterized in that, The temperature of the solvothermal reaction in step (1) is 78-82℃ and the time is 170-190min.

19. The preparation method according to claim 1, characterized in that, The pH of the solvothermal reaction system in step (1) is 10.8-11.

2.

20. The preparation method according to claim 1, characterized in that, The particle size D50 of the core precursor in step (1) is 3.2-4.0 μm.

21. The preparation method according to claim 1, characterized in that, The sintering in step (2) includes a first sintering in an air atmosphere, followed by a second sintering by switching to an oxygen atmosphere and continuing to heat up.

22. The preparation method according to claim 21, characterized in that, The temperature for the first sintering is 380-420℃, and the holding time is 3-5 hours.

23. The preparation method according to claim 21, characterized in that, The secondary sintering temperature is 740-760℃, and the holding time is 11-13h.

24. The preparation method according to claim 1, characterized in that, The molar ratio of the lithium source in step (2) to the precursor material in step (1) is (1.03-1.08):

1.

25. A core-shell rare-earth gradient-doped cathode material, characterized in that, The core-shell rare-earth gradient-doped cathode material is prepared by the preparation method according to any one of claims 1-24.

26. A lithium-ion battery, characterized in that, The lithium-ion battery includes the core-shell rare-earth gradient-doped cathode material as described in claim 25.

Citation Information

Patent Citations

  • Preparation method of ternary precursor containing Mg and Al

    CN106654197A

  • Bio-based carbon material modified ternary precursor as well as preparation method and application thereof

    CN119503911A